Timing synchronization and viterbi decoding for FPGA-based SDR platforms - Ayarde, Juan Martín (2019)
Fil: Ayarde, Juan Martín. Universidad Nacional de Córdoba. Laboratorio de comunicaciones digitales; Argentina.